2021
DOI: 10.1007/s41207-021-00251-w
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of SARS-Cov-2 and other enveloped viruses to the environment through protective gear: a brief review

Abstract: Over the past two decades, several deadly viral epidemics have emerged, which have placed humanity in danger. Previous investigations have suggested that viral diseases can spread through contaminants or contaminated surfaces. The transmission of viruses via polluted surfaces relies upon their capacity to maintain their infectivity while they are in the environment. Here, a range of materials that are widely used to manufacture personal protective equipment (PPE) are summarized, as these offer effective disinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The COVID-19 lockdown emerged as a reinstatement phase for nature highlighted in various studies ( Aravinthasamy et al, 2021 ; CPCB, 2021 ; Dutta et al, 2020a ; Karunanidhi et al, 2021 ; Khan et al, 2021a , 2021b ). The impact of COVID-19 lockdown gathered the attention of researchers across the globe ( Bhattacharya et al, 2021 ; Kumar et al, 2021 ; Petrosino et al, 2021 ), but none of the studies has attempted to analyse the status of air pollution after the unlocking of COVID-19 lockdown. The average AQI values obtained for the post lockdown phase (January 2021) have been illustrated using ArcGIS for representation purpose ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 lockdown emerged as a reinstatement phase for nature highlighted in various studies ( Aravinthasamy et al, 2021 ; CPCB, 2021 ; Dutta et al, 2020a ; Karunanidhi et al, 2021 ; Khan et al, 2021a , 2021b ). The impact of COVID-19 lockdown gathered the attention of researchers across the globe ( Bhattacharya et al, 2021 ; Kumar et al, 2021 ; Petrosino et al, 2021 ), but none of the studies has attempted to analyse the status of air pollution after the unlocking of COVID-19 lockdown. The average AQI values obtained for the post lockdown phase (January 2021) have been illustrated using ArcGIS for representation purpose ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“… De Rijcke et al, 2021 , Department for Environment Food & Rural Affairs (DEFRA) 2020 , Dzisi and Dei, 2020 , Eisen et al, 2007 , Epstein et al, 2006 , European Union (EU) 2020 , Food and Agriculture Organization (FAO) 2020 , Ferrarin et al, 2021 , García de Abajo et al, 2020 , Gola et al, 2021 , Greenbaum, 2018 , Grignani et al, 2020 , Gude and Muire, 2021 , Haddad et al, 2015 , Hirota, 2020 , Al-Gheethi et al, 2020 , Kasloff et al, 2021 , Katelaris et al, 2021 , Lacina and Goold, 2015 , Lacina and Hegedüs, 2020 , Langone et al, 2021 , Almilaji, 2021 , López-Feldman et al, 2021 , Maal-Bared et al, 2021 , Magazzino et al, 2020 , Mallapaty, 2021 , Marquès and Domingo, 2021 , Marquès et al, 2021 , Altamimi and Ahmed, 2020 , Martins et al, 2020 , Mauter and Fiske, 2020 , Medema et al, 2020 , Megahed and Ghoneim, 2021 , Missoni et al, 2020 , Amoroso et al, 2022 , Muraina, 2020 , Nardell, 2021 , Occupational Safety and Health Administration (OSHA) 2021 , Petrosino et al, 2021 , De Angelis et al, 2021 , Razzini et al, 2020 , Ren and Chen, 2021 , Arslan et al, 2020 , Rubin, 2020 , Sala-Comorera et al, 2021b , Sangkham et al, 2021 , Smith et al, 2014 , Staddon et al, 2020 , Suzán et al, 2009 , Achak et al, 2021 , Turner et al, 2020 , United Nations (UN) 2020 , Aygün and Tüfekçi, 2020 ,…”
Section: Uncited Referencesmentioning
confidence: 99%
“…This study also supports the point that there is no proper segregation system for different types of waste as there is in other countries. Petrosino (2021) found that many countries such as Afghanistan, Bangladesh, India, Indonesia (certain local governments), Japan, Kenya, Malaysia, Mexico, Nepal, South Africa, and Thailand (Chiang Rai) all have national legislation dictating trash segregation categories and a color-coding system for garbage bins. With color coding styles, it is easier for staff handling waste to put waste items into the correct container and maintain segregation of waste during transport, storage, treatment, and disposal.…”
Section: Separation Of Waste Materialsmentioning
confidence: 99%